Family Business Research in the Last Decade. A Bibliometric Review - Aparicio, Gloria; Ramos, Encarnación; Casillas, Jose-Carlos; Iturralde , Txomin (European Journal of Family Business, 2021)
This paper presents a bibliometric analysis of in family firms research, focusing on aspects that prior literature review studies did not fully understand or evaluate. It is based on the bibliometric evaluation of 3.368 scientific articles published from 2010 to 2020 in family firms (FF) as the title of the subject, keywords, and abstract. The authors discuss the results from the perspective of performance indicators and co-authorship visualization, giving a holistic bibliometric overview of the research topic. The field has attracted researchers and has led to the development of a wide body of literature. This study provides a synthesis and organization of existing knowledge on FF research.